EFEKTIVITAS REHABILITASI DAN POLA PEMBINAAN TERHADAP PECANDU NARKOTIKA DI BALAI BESAR REHABILITASI BADAN NARKOTIKA NASIONAL INDONESIA LIDO BOGOR - Dwi Afrimetty Timoera; Agus Martono (Jurnal Ilmiah Mimbar Demokrasi, 2016)
ABSTRACT This study aims to obtain empirical data, and reliable information about the effectiveness of rehabilitation and development patterns of the drug addict at the Center for Rehabilitation of the National Narcotics Agency Indonesia-Lido, Bogor. The method used is descriptive qualitative. The pattern of development in the institution more emphasis on behavior change, by conducting medical rehabilitation and social rehabilitation. Rehabilitation is divided into two major phases, namely the phase of medical rehabilitation and social rehabilitation phase. Medical rehabilitation includes detoxification and entry. While social rehabilitation phase includes primary phase and re-entry phase. Rehabilitation and development patterns are effective against drug addicts. This can be seen with the recovery rate of the resident and the resident's rate of return using drugs. But it is also influenced by many factors, both internal and external. Keywords: Rehabilitation, patteration, drug addicts.